Microfluidic SERS biosensor based on Au-semicoated photonic crystals for melanoma diagnosis - Wang, Weian (2025)
Surface-enhanced Raman scattering (SERS) shows great promise for early diagnosis due to its high specificity and rapid detection capabilities. However, its application is often hindered by substrate instability and insufficient interaction between the substrate and incident light. To address these challenges, a photonic-plasmonic strategy is often employed to enhance sensing performance but it is generally limited by the low efficiency of plasmonic metal and optical cavity resonances. In this study, we significantly improved resonance efficiency by optimizing the photonic crystal configuration and designing Au-semicoated polystyrene nanospheres. These modifications maximized light capture and resonance efficiency, resulting in a 790-fold enhancement of the Raman signal with a relative standard deviation of only 4.58%. This approach was further developed into microfluidic biosensors for melanoma diagnosis, achieving a 2-3 order-of-magnitude improvement over comparable SERS biosensors. We believe this technology has the potential to significantly improve the efficiency of early diagnosis and clinical medical analysis.